Pemetaan Penelitian Kompetensi Komunikasi Tahun 2009-2022 - Rakhmani; Muljono, Pudji; Lubis, Djuara P.; Sarwoprasodjo, Sarwititi (Jurnal ILMU KOMUNIKASI, 2024)
This study aims to map the communication competency research in 2009-2022. This study uses a systematic literature review with the keyword communication competence in the publish or perish application from the Scopus database for 2009-2022. Then, the articles were analyzed using Mendeley and Vosviewer. The results of the analysis found that the 2009-2022 communication competency research tends to be divided into two major groups, namely:  intercultural communication competence and communication competence. In addition, the development of communication competency research moved from  psychology and culture become the health and education. It were influenced by developments in communication and information technology.